Adivasi aesthetic knowing: A duographic account. Issue 3 (1st December 2016) - Hickman, Richard; Sinha, Pallawi
Using the different voices of the mentor and mentee, we engage with the notion of creating and conferring aesthetic significance as it occurs in the everyday lives of everyday peoples. We investigate how the arts empower marginalized 'voice' by enabling multimodal expressions and access to information that other methods may not elicit. This article takes the form of a 'duography', reporting an empirical study that focused upon an Adi Jan Jaati or Particularly Vulnerable Tribal Group (PVTG) of Jharkhand, in north-eastern India. In particular, we focus upon this indigenous community's epistemic and aesthetic practices. The article thus offers discussions on how aesthetic experiences and activities are essential means of being, of engagement and communication, and of (re)building trust with the community. We conclude by demonstrating the relevance of everyday aesthetics for the development of sustainable educational systems and future citizenship. Standing back, we acknowledge the reciprocal learning that occurs between the researcher and the 'researched', the doctoral student and supervisor.